miR-142 induces accumulation of reactive oxygen species (ROS) by inhibiting pexophagy in aged bone marrow mesenchymal stem cells - Houri, Kei (Sci Rep, 2020)
Elevation of the levels of reactive oxygen species (ROS) is a major tissue-degenerative phenomenon involved in aging and aging-related diseases. The detailed mechanisms underlying aging-related ROS generation remain unclear. Presently, the expression of microRNA (miR)-142-5p was significantly upregulated in bone marrow mesenchymal stem cells (BMMSCs) of aged mice. Overexpression of miR-142 and subsequent observation revealed that miR-142 involved ROS accumulation through the disruption of selective autophagy for peroxisomes (pexophagy). Mechanistically, attenuation of acetyltransferase Ep300 triggered the upregulation of miR-142 in aged BMMSCs, and miR-142 targeted endothelial PAS domain protein 1 (Epas1) was identified as a regulatory protein of pexophagy. These findings support a novel molecular mechanism relating aging-associated ROS generation and organelle degradation in BMMSCs, and suggest a potential therapeutic target for aging-associated disorders that are accompanied by stem cell degeneration.